The question on this form is incorrect if the first term is y''' , the auxiliary equation does not has solution . So i will solve the equation on the form
"y''+y'+y=0"
Set up and solve the auxiliary equation
"\\begin{aligned}m^2+m+1&=0\\\\\n\\end{aligned}"
Then
"m=\\frac{-1\\pm \\sqrt{1-4}}{2}=\\frac{-1}{2}\\pm \\frac{\\sqrt{3}}{2}i"
Here "\\alpha =-1\/2,\\ \\ \\ \\beta= \\sqrt{3}\/2" , then the solution given by
"\\begin{aligned}\ny&=e^{\\alpha x} [c_1\\cos \\beta x+c_2\\sin \\beta x]\\\\\n&= e^{(-1\/2)x}[c_1\\cos (\\sqrt{3}\/2) x+c_2\\sin(\\sqrt{3}\/2) x]\n\\end{aligned}"
---------------------------------------------------------------------------------------------------------------------------------------------
If the equation written true as
"y''+y''+y=0\\ \\ \\to 2y''+y=0"
Set up and solve the auxiliary equation
"2m^2+1=0"
Then "m=\\pm \\frac{1}{\\sqrt{2}}" , here "\\alpha =0,\\ \\ \\beta = 1\/\\sqrt{2}," then the solution given by
"\\begin{aligned}\ny&=e^{\\alpha x} [c_1\\cos \\beta x+c_2\\sin \\beta x]\\\\\n&= [c_1\\cos (1\/\\sqrt{2}) x+c_2\\sin(1\/\\sqrt{2}) x]\n\\end{aligned}"
Comments
Leave a comment